Ingesting a fermented milk product reduces liver triacylglycerol accumulation and normalizes gut permeability in rats even under a cholic acid-fed condition. (May 2023) - Lee, DongGeun; Iwasaki, Wakana; Hori, Shota; Kubota, Natsuki; Ishizuka, Satoshi
Graphical abstract: Highlights: A diet containing a fermented milk product (FMP) reduces food intake in rats. FMP diet reduces hepatic triacylglycerol (TG) levels in cholic-acid (CA)-fed rats. Enhanced in vivo gut permeability induced by CA was inhibited by the FMP diet. FMP diet enhances the fecal excretion of TG and non-12-hydroxylated bile acids. Abstract: We investigated whether a diet containing fermented milk products (FMP) improves hepatic lipid accumulation and gut permeability induced by cholic acid (CA) supplementation. After acclimation, male Slc:Wistar rats were fed diets supplemented with a combination of FMP and/or CA (0.5 g/kg diet) for four weeks. FMP was used as a protein source. The FMP-containing diet reduced the total food intake and hepatic triacylglycerol levels without altering the body weight. Enhanced in vivo gut permeability induced by CA was inhibited by the FMP diet. The FMP diet also enhanced the excretion of fecal triacylglycerol and the fecal concentration of non-12-hydroxylated BAs. Multiple regression analysis revealed that total food intake, fecal deoxycholic acid concentration, and fecal triacylglycerol excretion were predictors of hepatic triacylglycerol concentration. A negative correlation was observed between fecal non-12-hydroxylated BAs and hepatic triacylglycerol concentration. These results imply that FMP contributes to reduced hepatic lipid accumulation and normalised gut permeability.